Benefit finding and well-being in older adults: The utility of the General Benefit Finding Scale. - Tony Cassidy; Ingrid Doyle (International Journal of Psychological Research, 2018)
The research aim was to test the General Benefit Finding Scale (GBFS) in a cross-sectional survey of adults aged 55 years and older and to assess to what extent it relates to mental well-being, perceived social support, health and personality. Participants (n=341) completed a questionnaire which included demographic questions, the GBFS, and measures of mental well-being, perceived social support, activity levels, and personality. Benefit finding was higher in older adults and correlated positively with mental well-being and perceived support. The impact of the psychosocial factors investigated on benefit finding levels was small (9.2%) with mental well-being, sex and agreeableness being significant predictors. The study provides additional support for the use of the GBFS and suggests that perceived social support, particularly from friends, is especially important for older adults.